Investigation on pharmacokinetics, tissue distribution and excretion of a novel platinum anticancer agent in rats by Inductively Coupled Plasma Mass Spectrometry (ICP-MS). (14th February 2014) - Zhao, Jie; Wen, Yanli; Zhang, Wei; Zhao, Di; Fan, Ali; Zhang, Yongjie; Deng, Shuhua; Wang, Xin; Liu, Qingwang; Lu, Yang; Wang, Zhimei; Gou, Shaohua; et al.
Abstract: 1. DN604 is a new platinum agent with encouraging anticancer activity. The present study was to explore the pharmacokinetic profiles, distribution and excretion of platinum in Sprague–Dawley rats after intravenous administration of DN604. A sensitive and selective inductively coupled plasma mass spectrometry (ICP-MS) method was established for determination of platinum in biological specimens. The pharmacokinetic parameters were calculated by a non-compartmental method. 2. The area under concentration–time curve AUC0−t and AUC0−∞ for platinum originating from DN604 at 10 mg/kg were 25.15 ± 1.29 and 28.72 ± 1.04 μg/hml, respectively. The mean residence time MRT was 36.59 ± 6.65 h. The volume of distribution Vz was 11.42 ± 2.49 l/kg and clearance CL was 0.18 ± 0.01 l/h/kg. In addition, the elimination half-life T1/2z was 44.83 ± 9.75 h. After intravenous administration of DN604, platinum was extensively distributed in most of tested tissues except brain. The majority of platinum excreted via urine, and its accumulative excretion ratio during the period of 120 h was 63.5% ± 7.7% for urine, but only 6.94% ± 0.11% for feces. 3. The satisfactory half-life, wide distribution and high excretion made this novel platinum agent worthy of further research and development.